Surrogate worth trade-off method for economic-emission dispatch - Singh, L.; Dhillon, J.S. (2006 Power Systems Advanced Metering, Protection, Control, Communication, and Distributed Resources : 14-17 March 2006, 2006)
The economic-emission dispatch (EED) problem is a multiple non-commensurable objective problem that minimizes both cost and emission together subject to power balance and generators capacity constraints. In this paper, multiobjective economic-emission dispatch problem is converted into a scalar optimization problem. Scalar optimization problem is solved many times for a different set of weight pattern to generate non-inferior solutions along with trade-off functions between the conflicting objectives. Fuzzy decision making theory is exploited to decide the best compromise solution. The optimal solution is obtained by considering real and reactive power losses, which are calculated by performing fast decoupled load flow analysis. The validity of the proposed method is demonstrated on 25-bus, 35-lines IEEE system, comprising of five generators